(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The faculty plays a number of roles in teaching. They are consistent patterns of behaviors that guide and direct our thoughts and behaviors to specific situations. Teachers may assume the role of a consultant, resource person, model, facilitator, prescriptive and advisor. When a teacher is flexible, he is able to assume various roles pertaining to the demands of particular situations. Teacher plays a major role in the maintenance, sustenance and enhancement of quality education in India.Educator with personal model style has confidence in instructing individuals by illustrations and builds up a model for how to think and carry on. He administers, manages and guides by demonstrating to get things done, and urging understudies to watch and then to copy the teachers approach.Educator with delegator style is worried with creating understudies ability to work in a self-sufficient design. Understudies work freely on ventures or as a major aspect of self-sufficient groups. The educators are accessible at the demand of understudies. An instructor may make them show style as most ruling and other style as less ruling. In this manner an educator may show a profile of different instructing styles.